Pelatihan Pembuatan Video Pembelajaran Literasi Numerasi Siswa Slow Learner Bagi Guru Pendamping Khusus SMP Inklusi Kabupaten Magetan - Sri Anardani; Wasilatul Murtafiah; Rischa Pramudia Trisnani (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Inclusive education is one of the efforts to realize educational services for children with special needs as regulated in Permendiknas No. 70 of 2009. Magetan Regency was declared an inclusion district in 2017. Based on the 2023 education report card data, junior high school students have the lowest achievement in numeracy literacy compared to elementary and high school students, namely only 41.14%, almost close to the poor category (<40%). Based on the results of interviews with Special Assistant Teachers (GPK), data was obtained that slow learner students had difficulty using writing in the Mathematics learning process. The training activity for making learning videos using OpenShoot videos was carried out using direct practice, mentoring and evaluation methods. The aim of the training is to develop GPK's digital competency. The result of this training is learning media in the form of numeracy literacy learning videos for slow learner students.